Process Parameter Optimization for Resistance Spot Welding Using Response Surface Methodology - Rawal, Manjunath R.; Varane, Vaibhav; Kolhapure, Rakesh R. (Asian Review of Mechanical Engineering, 2018)
Quality of product and process are mainly depends upon their process parameters and their levels selected for design and manufacturing. So, it is important to decide optimal levels of process parameters to get desired output variables. The study focuses on finding out optimal levels of process parameters in Resistance Spot Welding (RSW)and its effect on tensile strength and nugget diameter. The Response Surface Methodology (RSM) is employed for multi objective optimization of responses for maximizing tensile strength and minimizing nugget diameter. Response optimizer with desirability function is found for optimum results of response surface methodology. Analysis of variance (ANOVA) is carried out for analyzing contribution of each process parameter on the performance of RSW.